Brothers in arms in the European car wars: Management-labour pacts in the context of regime competition - Stefan Zagelmeyer (Max Planck Institute for the Study of Societies, 2000)
During the 1990s, virtually all major European car companies arrived at company-level collective agreements on employment and competitiveness. In brief, these pacts aim at maintaining or creating jobs and at improving the competitiveness of the plant or company in inter- as well as intracompany competition. This paper first presents two approaches to analyse such employment pacts. It then introduces selected cases of company-level employment pacts in the European car industry. The main part of the paper analyses these employment pacts and discusses their implications for labour relations. The author concludes that the employment pacts in the European car industry may not just be seen as examples of concession bargaining, but rather as new, emerging forms of cooperative and consensual labour relations, which are about adjusting the governance of the employment relationship to the imperatives of joint competitive success.
Keywords: 300